ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN KAP PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kelvin, Kelvin; Prima, Argo Putra (SCIENTIA JOURNAL, 2021)
Currently the company's growth is very fast, making the role of KAP very important so that it will increase the number of KAP. With the increase in the number of KAP, it will create competition and will not rule out the possibility for companies to change KAP. The purpose of this research is to examine the effect of management change, audit opinion and public accountant firms size on auditor switching. The object of this research is the manufacture companies listed on the Indonesian Stock Exchange for the period 2015-2019. The sample was selected by purposive sampling method with the result obtained by 130 companies. The research data uses secondary data through the website www.idx.co.id. The research method used logistic regression analysis. Testing data using the SPSS v.25 application. The result of this study indicate that management change partially has no affect on auditor switching, while audit opinion and public accountant firms size partially affect auditor switching. The test result also show that the management change, audit opinion and public accountant firms size variables simultaneously affect auditor switching with a determination value of 26,8%, while 73,2% is influenced by other variables apart from the independent variables in this study.